Penguatan Pendidikan Karakter Pada Peserta Didik Melalui Karya Ontologi Puisi Di SMA Kota Pontianak - Sariani Sariani; Aunnurrahman Aunnurrahman; Halida Halida (Journal on Education, 2023)
The emergence of intense discussions about character formation is being widely discussed in the world of Indonesian education. Issues such as bullying, violence, intolerance, pornography, elements of SARA, corruption, manipulation, lies in the world of education ranging from cheating on exams to plagiarism, as well as the lack of role models among state leaders, are all actually related to character issues. In an effort to implement character education in an educational institution, the values of character education can be instilled in the learning process of implementing the project based learning model or included in literacy activities in language month activities through students' poetry anthology works by creating works without containing elements of SARA, pornography, bullying, violence and intolerance. This research was conducted using literature study to explore the character education taught in Indonesian language learning in high schools in poetry anthologies. This study concludes that in implementing Indonesian language learning, teachers need to understand the concept of character education and act as curriculum implementers and facilitators for students at school. This aims to ensure that students not only have good competence, but also have commendable behavior.